Conceptualization Of A Learning Design To Prepare Teachers For Technology Integration - Kritika Gosain (International Journal of Advanced Science and Technology, 2020)
The advancement in information and communication technologies has altered the way human lives. Today, technology has incorporated into all fields of work. The teachers all over the globe are also encouraged to integrate technology into their teaching. The adoption of technologies by the teachers requires techno-pedagogic competencies. This study focuses on conceptualizing and testing a learning design for developing techno-pedagogic competencies among pre-service teachers to prepare them for technology integration. The design-based research methodology is adopted for the study. The conceptualization of the learning design is grounded on the guidelines of the Learning Design Conceptual Map. The conceptualized learning design is tested by one group pre-test post-test experimental design. The learning design is administered on 36 pre-service teachers, who are enrolled in a two-year Bachelor in Education (B.Ed.) programme. The findings of the study revealed that the learning design has strongly affected the development of the techno-pedagogic competencies among the pre-service teachers as the mean score for the post-test of pre-service teachers on the techno-pedagogic competencies differ significantly from that of the pre-test.